Stages of Environmental Awareness Among Visitors of a Peri-Urban Nature Reserve in Mexico - Chávez-Vizcarra, Renata (2024)
[Introduction]: Natural parks with a recreational vocation play a fundamental role in promoting pro-environmental actions among their visitors. However, for the Latin American region, the programs aimed at these purposes have not achieved the expected results. On the contrary, one of the causes that have intensified the environmental deterioration of the parks is recreational activities. One of the major challenges to promote conservation in these areas is the development of environmental awareness among visitors. [Objective]: The study aimed to analyze the stages of environmental awareness of 190 visitors to Sierra Morelos State Park, a natural protected area in the municipality of Toluca, State of Mexico, to support management that strengthens conservation, generates attitudes, and involves visitors in pro-environmental practices. [Methodology]: In order to collect data, a structured questionnaire was designed based on the four dimensions of environmental awareness: cognitive, affective, conative and active. This study conducted a factor analysis, a cluster analysis, and a Kruskal-Wallis test to identify differences between groups. [Results]: Eleven factors were identified, explaining 70.88 % of the cumulative variance. The cluster analysis identified three groups: Stage 1: passive discursive-intentional; Stage 2: environmental predisposition; Stage 3: affective of agreed actions. [Conclusions]: The results show that there is no definite number of stages that explain one or several realities for which human experiences are the key to environmental awareness.